Influence of core substitution on the electronic structure of benzobisthiadiazoles - Ajdari, Mohsen; Pappenberger, Ronja; Annweiler, Caja; Kaczun, Tobias; Müller, Leon; Winkelmann, Larissa; Ahrens, Lukas; Bunz, Uwe H. F.; Dreuw, Andreas; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2024)
Benzobisthiadiazoles (BBTs) are promising organic semiconductors for applications in field effect transistors and solar cells since they possess a strong electron-accepting characteristic. Thereby, the electronic structure of organic/metal interfaces and within thin films is essential for the performance of organic electronic devices. Here, we study the structural and electronic properties of two BBTs, with different core substitution patterns, a phenyl (BBT-Ph) and a thiophene (BBT-Th) derivative adsorbed on Au(111) using vibrational and electronic high-resolution electron energy loss spectroscopy in combination with state-of-the-art quantum chemical calculations. In the mono- and multilayer, both BBTs adopt a planar adsorption geometry with the molecular backbone, as well as the phenyl and thiophene side groups are oriented parallel to the gold substrate. The energies of the lowest excited electronic singlet states (S) and the first triplet state (T1) are determined. The optical gap (S0 → S1 transition) is found to be 2.2 eV for BBT-Ph and 1.6 eV for BBT-Th. The energy of T1 is identified to be 1.2 eV in BBT-Ph and in the case of BBT-Th 0.7 eV. Thus, both the optical gap size as well as the T1 energy are drastically reduced in BBT-Th compared to BBT-Ph. Based on our quantum chemical calculations, this is attributed to the electron-rich nature of the five-membered thiophene rings in conjunction with their preference for planar geometries. Variation of the substitution pattern in BBTs opens an opportunity for tailoring their electronic properties.
Online veröffentlicht: 28. Februar 2024
Gesehen am 11.07.2024